(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
Scientific progress and the rapid increase in the results of human creativity are the greatest evidence of the role played by creative thinking and proactive work in the development of human societies, and the strength of society lies in its creative and constructive intellectual power resulting from human resources, the most important element to reach the desired goals and objectives, and the role of women must be essential and pivotal, and their importance lies in their influential role to raise the efficiency of health institutions. The research aimed to identify the contribution of women in hospitals in Latakia Governorate, and the creativity and proactivity of working women and their role in improving the reality of health services provided in government hospitals in Latakia Governorate. The research adopted the descriptive analytical approach, 385 questionnaires were distributed, 377 questionnaires were recovered, 7 questionnaires were rejected for incomplete answers, and the final number subject to analysis reached 370, appropriate statistical methods were used, in order to reach the most important recommendations, the most important of which are: Attention to training, developing creative skills, building proactive capabilities, motivating creative women, support outstanding and creative ideas to solve problems